From Hill to Residential Space, Meteseh-Semarang 1987-2000: Transformation of Suburban Space - Budita, Carissa Almaasah; Wijayati, Putri Agus (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study aims to produce a narrative about the process of suburban spatial transformation that occurred in Meteseh-Semarang from 1987 to 2000. The area that was originally hills and agricultural fields changed into a residential area along with increasing urbanization and urban expansion. The increasing need for housing drove this change, the influx of property capital, and spatial planning policies that opened up access to development in suburban areas. This study uses a historical method consisting of heuristics, source criticism, interpretation, and historiography using primary sources from Suara Merdeka, Abadi, and Analisa newspapers to reveal the social, economic, and political dynamics that influence the conversion of land from agrarian to residential, and its impact on the local community. The study results show that urbanization in Meteseh changes the physical landscape and triggers social dislocation, spatial segregation, and inequality of access between old residents and newcomers. These findings confirm that the development of suburban areas cannot be separated from market logic and the dominance of formal and informal actors in the production of space. Therefore, this research contributes to understanding the social history of urbanization and the urgency of more inclusive and equitable urban planning.